THEORETICAL ASPECTS OF THE USE OF PROFESSIONAL SUBJECTIVITY OF FUTURE LINGUISTS BY THE TECHNOLOGY OF DEVELOPING CRITICAL THINKING - Шуйншкалиев, Заманбек (Вестник ЗКУ, 2024)
The article analyzes the methods of using critical thinking technology in order to improve the linguistic competence of students. The issue of the effectiveness of using critical thinking technology to form the communicative competence of students of non-linguistic universities in teaching a foreign language.